Multiple Classifier Systems 8th International Workshop, MCS 2009, Reykjavik, Iceland, June 10-12, 2009, Proceedings - Benediktsson, Jón Atli; Kittler, Josef; Roli, Fabio (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2009)
This book constitutes the refereed proceedings of the 8th International Workshop on Multiple Classifier Systems, MCS 2009, held in Reykjavik, Iceland, in June 2009. The 52 revised full papers presented together with 2 invited papers were carefully reviewed and selected from more than 70 initial submissions. The papers are organized in topical sections on ECOC boosting and bagging, MCS in remote sensing, unbalanced data and decision templates, stacked generalization and active learning, concept drift, missing values and random forest, SVM ensembles, fusion of graphics, concepts and categorical data, clustering, and finally theory, methods and applications of MCS.